2018
DOI: 10.1074/jbc.m117.809236
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine regulates fatty acid and lipid metabolism in yeast

Abstract: S-Adenosyl-l-homocysteine hydrolase (AdoHcy hydrolase; Sah1 in yeast/AHCY in mammals) degrades AdoHcy, a by-product and strong product inhibitor of S-adenosyl-l-methionine (AdoMet)-dependent methylation reactions, to adenosine and homocysteine (Hcy). This reaction is reversible, so any elevation of Hcy levels, such as in hyperhomocysteinemia (HHcy), drives the formation of AdoHcy, with detrimental consequences for cellular methylation reactions. HHcy, a pathological condition linked to cardiovascular and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…5). This data strongly supports the recent findings of S-adenosyl homocysteine as the key trigger of lipid deregulation (Visram et al 2018). As a response to Cd stress, the host cell's defence mechanism activates UPR transcription factor and UPR genes and proteins (Table 2) (Gardarin et al 2010;Wysocki and Tamás 2010;Rajakumar et al 2016a).…”
Section: Upregulation Of Sulphur Assimilation Pathway and Uprsupporting
confidence: 90%
See 1 more Smart Citation
“…5). This data strongly supports the recent findings of S-adenosyl homocysteine as the key trigger of lipid deregulation (Visram et al 2018). As a response to Cd stress, the host cell's defence mechanism activates UPR transcription factor and UPR genes and proteins (Table 2) (Gardarin et al 2010;Wysocki and Tamás 2010;Rajakumar et al 2016a).…”
Section: Upregulation Of Sulphur Assimilation Pathway and Uprsupporting
confidence: 90%
“…When cells were subjected to Cd toxicity, MET transcriptional factors like MET4, MET28, MET31, and MET32 were upregulated (Hosiner et al 2014), indicative of significant links to the sulphur and methyl cycle genes (Tables 3 and 4). SAM regulated de novo PC synthesis genes such as CHO2 and OPI3 that controlled the major membrane phospholipids, PC and PE, in both yeast and mammals (Visram et al 2018). Deletion of CHO2 and OPI3 induced lipid alterations including TAG, LD accumulation, increased FA content, and altered FA profiles in yeast (Rajakumar et al 2016a).…”
Section: Upregulation Of Sulphur Assimilation Pathway and Uprmentioning
confidence: 99%
“…Baszczuk et al [ 42 ] reported that a daily administration of 15 mg of folic acid led to a considerable decrease in homocysteine levels, and a substantive increase in HDL-C levels in the patients with primary hypertension. In yeast cells, homocysteine supplementation increased cellular fatty acid and TG contents, induced a shift in fatty acid composition, and decreased the condensing enzymes involved in very long-chain fatty acid synthesis [ 43 ]. Secondly, the rs1801133 polymorphism may modulate the lipid metabolism by affecting the methylation state of DNA or proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular LDs store a wide distribution of lipid molecules and lipid metabolism directly alters the lipid composition of LDs. 30,31 The field of lipidomics aims to study changes in lipid metabolism in response to physiological, pathological, and environmental conditions by characterizing this compositional distribution of all cellular lipids.…”
Section: Introductionmentioning
confidence: 99%